2015
DOI: 10.1186/s12929-015-0142-2
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation similarities in genes of black South Africans with systemic lupus erythematosus and systemic sclerosis

Abstract: BackgroundSystemic lupus erythematosus (SLE) and systemic sclerosis (SSc) are systemic autoimmune connective tissue diseases that share overlapping clinico-pathological features. It is highly probable that there is an overlap in epigenetic landscapes of both diseases. This study aimed to identify similarities in DNA methylation changes in genes involved in SLE and SSc. Global DNA methylation and twelve genes selected on the basis of their involvement in inflammation, autoimmunity and/or fibrosis were analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 61 publications
5
25
1
1
Order By: Relevance
“…Altorok et al performed a genome-wide DNA methylation analysis in SSc patients with diffuse or limited disease, as well as age-, sex-, and ethnicity- matched healthy controls using the Illumina Infinium Human Methylation 450 BeadChip array, which covers over 485,000 CpG sites in the entire genome [97]. A total of 2710 and 1021 differentially methylated CpG sites were identified in diffuse SSc and limited SSc, respectively, with a large proportion of them being hypomethylated (61% in diffuse and 90% in limited), agreeing with previous studies that showed global hypomethylation in various cell types, including fibroblasts, in SSc [79, 85, 98]. This unbiased approach identified genes that were affected by DNA methylation in SSc including ones that encode collagen, ECM, transcription factors, as well as genes that are involved in the TGFβ pathway and Wnt pathway (listed in Table 3), echoing and expanding the results from hypothesis-driven studies mentioned earlier.…”
Section: Epigenetic Impact In Ssc Pathogenesissupporting
confidence: 77%
See 1 more Smart Citation
“…Altorok et al performed a genome-wide DNA methylation analysis in SSc patients with diffuse or limited disease, as well as age-, sex-, and ethnicity- matched healthy controls using the Illumina Infinium Human Methylation 450 BeadChip array, which covers over 485,000 CpG sites in the entire genome [97]. A total of 2710 and 1021 differentially methylated CpG sites were identified in diffuse SSc and limited SSc, respectively, with a large proportion of them being hypomethylated (61% in diffuse and 90% in limited), agreeing with previous studies that showed global hypomethylation in various cell types, including fibroblasts, in SSc [79, 85, 98]. This unbiased approach identified genes that were affected by DNA methylation in SSc including ones that encode collagen, ECM, transcription factors, as well as genes that are involved in the TGFβ pathway and Wnt pathway (listed in Table 3), echoing and expanding the results from hypothesis-driven studies mentioned earlier.…”
Section: Epigenetic Impact In Ssc Pathogenesissupporting
confidence: 77%
“…They reported that Th17-specific transcription factors, RORC1 and 2, were hypermethylated in PBMCs. The DNA methylation results obtained from whole blood [85] was similar to what was published in CD4+ T cells: FOXP3 and CD70 were hypomethylated, however CD11a was hypermethylated instead, pointing to the importance of examining epigenetic changes in individual cell types. These studies suggest an epigenetic impact on immune dysregulation in SSc.…”
Section: Epigenetic Impact In Ssc Pathogenesissupporting
confidence: 56%
“…SSc is a systemic disease and involves multiple organs, tissues, and cell types. Previous data were generated from fibroblast [ 13 , 14 ], purified CD4 + T cells [ 8 , 14 , 15 ], whole blood cells [ 16 ], and skin biopsy [ 17 ]. Peripheral blood mononuclear cells (PBMCs) represent a broad spectrum of cell types including T cells, B cells, NK cells, monocytes, and dendritic cells, which all played major roles in immunological events.…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxia can directly methylate Thy-1 promoter region to downregulate its expression in lung fibroblasts (80). In contrast to pulmonary fibrosis, Thy-1 is found hypomethylated in black South Africans with systemic lupus erythematosus (84). …”
Section: Dna Methylation In Pulmonary Fibrosismentioning
confidence: 99%